Interaction of tumor‑associated macrophages with stromal and immune components in solid tumors: research progress (Review) - Kazakova, Anna; Sudarskikh, Tatiana; Kovalev, Oleg; Kzhyshkowska, Julia; Larionova, Irina (International journal of oncology, 2023)
Tumor‑associated macrophages (TAMs) are crucial cells of the tumor microenvironment (TME), which belong to the innate immune system and regulate primary tumor growth, immunosuppression, angiogenesis, extracellular matrix remodeling and metastasis. The review discusses current knowledge of essential cell‑cell interactions of TAMs within the TME of solid tumors. It summarizes the mechanisms of stromal cell (including cancer‑associated fibroblasts and endothelial cells)‑mediated monocyte recruitment and regulation of differentiation, as well as pro‑tumor and antitumor polarization of TAMs. Additionally, it focuses on the perivascular TAM subpopulations that regulate angiogenesis and lymphangiogenesis. It describes the possible mechanisms of reciprocal interactions of TAMs with other immune cells responsible for immunosuppression. Finally, it highlights the perspectives for novel therapeutic approaches to use combined cellular targets that include TAMs and other stromal and immune cells in the TME. The collected data demonstrated the importance of understanding cell‑cell interactions in the TME to prevent distant metastasis and reduce the risk of tumor recurrence.